Effect of the Training of Nurses on the Reduction of Noise Pollution in Intensive Care Units - Z Godarzi; F Oskouie; K Azam; M Monazzam; T Loni; J Ghasemi; M Ahmadpoor (Iran University of Medical Sciences, 2019)
Background & Aims: Noise pollution is becoming a severe issue for the patients admitted in intensive care units (ICUs). For the reduction of noise pollution in hospitals, researchers recommend proper training and adherence to protocols. The present study aimed to assess the effect of the training of nurses on the reduction of noise pollution in ICUs. Materials & Methods: This clinical trial was conducted at Tehran University of Medical Sciences and Iran University of Medical Sciences, which were randomly selected as the intervention and control groups, respectively. Before the intervention, noise intensity was measured at four locations inside the ICUs of the selected universities (entrance and exit, nursing stations, center of the department, and patients' bedside). Afterwards, methods for the control of noise pollution were introduced to the nurses in the intervention group in the form of a training workshop. Two months after the intervention, noise intensity was measured in the selected locations in the intervention and control groups. Noise intensity was measured using a sound meter in decibels (dB), and the dB-scale sound pressure level in LA networks (corresponding to the hearing of humans) was measured every two hours for three consecutive days.  Results: According to the results of paired t-test, the intra-group effects of training regarding the correlation of the mean and standard deviation of the sound pressure level was estimated at 55.37±5.43 and 57.79±4.96 in the intervention group before and after the intervention, respectively, which indicated a significant difference in this regard (P<0.001). In addition, comparison of the intervention and control groups using independent t-test indicated a significant difference between the groups before and after the intervention (P<0.001). Also, the result of covariance test was not significant in intervention group and control group. Conclusion: According to the results, the training of nurses on the control of noise pollution was effective in the reduction of this issue. Therefore, it is recommended that noise pollution in hospitals be reduced through implementing in-service training workshops for nurses, asking nurses to be quite and promote sleep, and exploit silence signs in ICUs.